The impact of a mobile money-based intervention on maternal and neonatal health outcomes in Madagascar: cluster-randomized controlled trial - Bogler, Lisa; Vieira, Bítia; Andriamasy, Harizaka Emmanuel; Rampanjato, Zavaniarivo; Vollmer, Sebastian; Bärnighausen, Till; Ralisimalala, Andriamampianina; Emmrich, Julius; Knauss, Samuel (JMIR public health and surveillance, 2025)
Background: Financial barriers to accessing obstetric care persist in many low-resource settings. With increasing use of mobile phones, mobile money services appear as a promising tool to address this concern. Maternal health care is particularly suitable for a savings program using mobile money due to the predictable timing and costs of delivery. The mobile money-based Mobile Maternal Health Wallet (MMHW) intervention aimed to ease the burden of out-of-pocket expenses related to maternal health care by providing an accessible savings tool. - Objective: This study aimed to assess the impact of the MMHW on maternal and neonatal health outcomes. - Methods: We used a stratified cluster-randomized trial to assess the impact of the MMHW on maternal and neonatal health outcomes in the Analamanga region of Madagascar. All 63 eligible public sector primary care health facilities (Centres de Santé de Base [CSBs]) within 6 strata were randomized to either receive the intervention or not. We estimated intention-to-treat effects and contamination-adjusted effects following an instrumental variable approach. The primary outcomes included (1) delivery at a health facility, (2) antenatal care visits, and (3) total health care expenditure. Between March 2022 and December 2022, a total of 6483 women who had been pregnant between July 2020 and December 2021 were surveyed. - Results: Among women in catchment areas of treated CSBs, 38.79% (1297/3344) had heard of the MMHW, and 37.42% (485/1296) of them registered for the tool. There was considerable variation in uptake across treated CSBs. Descriptively, women in the catchment areas of treated CSBs were more likely to deliver in a facility and had more antenatal care visits and higher total health expenditures compared to women in control CSB catchment areas in the intention-to-treat and contamination-adjusted analyses. However, none of the effects were statistically significant. - Conclusions: While this study did not identify a statistically significant impact, the estimated contamination-adjusted effects suggest that the MMHW has potential to improve access to maternal care for women who are receptive to such a mobile money-based savings tool. Estimated population-level effects were much smaller, and this study was underpowered to detect such effects due to lower-than-anticipated uptake of the intervention. - Trial Registration: German Clinical Trials Register DRKS00014928; https://www.drks.de/search/de/trial/DRKS00014928